The International Classification of Headache Disorders from the point of view of Thomas Kuhn: a reflection - Pagliarin, Luis Gustavo; Pegoraro de Almeida, João Carlos; de Assis César, Alcântara Ramos (Headache Medicine, 2023)
Headaches are characterized by a sensation of discomfort or pain in the cephalic region. Due to the large number of types and subtypes of headaches, the standardization of their approach is necessary through the International Classification of Headache Disorders (ICHD), a document that is currently in its 3rd edition (ICHD-3). The evolution of the ICHD follows the hypothetical-deductive model of science based on Karl Popper's philosophy, which has a strong presence in the health sciences. The classification of headaches has evolved over time, incorporating and removing criteria, reflecting the need to adapt the classification to constantly evolving scientific and clinical demands. However, some changes can generate discrepancies between clinical practice and the elaborated diagnostic tools. In this context, this article reflects on whether it would be advantageous to return to old principles and foundations of obsolete classifications. The criterion of osmophobia, which is no longer in use in ICHD-3, is highlighted. This reflection can be developed following Thomas Kuhn's (1922-1996) view on science. In his main work, "The Structure of Scientific Revolutions" (1962), Kuhn proposes a three-stage model for science: the adoption of a paradigm, normal science, and a period of crisis. Kuhn also proposes the principle of incommensurability to understand the limitations and complexities of science. The application of this principle allows headache specialists to recognize that different approaches to headache classification have their own limitations and complexities, encouraging them to consider a variety of perspectives, paradigms, and theories in approaching clinical cases and conducting scientific studies. An integrative approach that combines Popper's hypothetical-deductive model with Kuhn's principle of incommensurability allows headache specialists to have a broader and more critical understanding of headache classifications.